2012
DOI: 10.1096/fj.11-202184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modulation of airway epithelial ciliary response to sneezing

Abstract: Our purpose was to evaluate the effect of the mechanical force of a sneeze on sinonasal cilia function and determine the molecular mechanism responsible for eliciting the ciliary response to a sneeze. A novel model was developed to deliver a stimulation simulating a sneeze (55 mmHg for 50 ms) at 26°C to the apical surface of mouse and human nasal epithelial cells. Ciliary beating was visualized, and changes in ciliary beat frequency (CBF) were determined. To interrogate the molecular cascades driving sneeze-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 54 publications
2
71
0
Order By: Relevance
“…Because taste receptors are linked to downstream calcium signaling, we loaded mouse septal ALI cultures with the calcium-sensitive fluorophore Fluo-4 to measure relative changes in cytoplasmic free calcium concentration as previously reported. 36 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because taste receptors are linked to downstream calcium signaling, we loaded mouse septal ALI cultures with the calcium-sensitive fluorophore Fluo-4 to measure relative changes in cytoplasmic free calcium concentration as previously reported. 36 …”
Section: Resultsmentioning
confidence: 99%
“…Calcium and nitric oxide imaging were performed as previously described 14, 36 using the calcium sensitive fluorophore Fluo-4 and reactive nitrogen species indicator DAF-FM, respectively. The validation of DAF-FM use as a method for measuring NO produced by sinonasal ALI cultures was previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Other receptors also regulate mucociliary clearance, including, e.g., the bitter taste receptor (T2R) T2R38 (discussed below in Regulation of Antimicrobial Compounds) that binds bacterial metabolites 23 and those receptors that respond to mechanical stimulation. 24 Studies found that dehydrated mucus, as occurs in patients with cystic fibrosis, 22,25,26 and increased mucus production 27 can lead to mucociliary clearance dysfunction. Abnormalities that affect epithelial cilia function may also result in impaired mucociliary clearance.…”
Section: Mucociliary Clearance: Mopping Away Bugs and Debrismentioning
confidence: 99%
“…Stock solutions of chemicals were dissolved in dimethyl sulfoxide before dissolving in Dulbecco's phosphate-buffered saline (PBS), with the highest working concentrations reflecting no more than 0.1% dimethyl sulfoxide, a level that does not affect sinonasal ALIs. 19,20,42,43 In the experiments, PBS was primarily used on the apical side and Hank's Balanced Salt Solution (which contained 10 mM HEPES and Minimal Essential Medium amino acids) basolaterally, as described elsewhere. 19,20,[42][43][44] 4-Amino-5-methylamino-2Ј,7Ј-difluroescein (DAF-FM) was from Life Technologies, Inc. (Carlsbad, CA).…”
Section: Solutions and Reagentsmentioning
confidence: 99%